A molecular revolution in the study of intestinal microflora. Issue 2 (11th January 2006) - Furrie, E
Abstract : Bacterial colonisers of the colon comprise several hundred bacterial species that live in a complex ecosystem. Study of this complex ecosystem has been carried out, until recently, by traditional culture techniques with biochemical methods to identify organisms. The development of molecular techniques to investigate ecological microbial communities has provided the microbiologist with a vast array of new techniques to investigate human intestinal microflora. Metagenomics, the science of biological diversity, combines the use of molecular biology and genetics to identify and characterise genetic material from complex microbial environments. The combination of metagenomics and subsequent quantitation of each identified species using molecular techniques allows the relatively rapid analysis of whole bacterial populations in human health and disease